IMPROVING THE EFFICIENCY OF IMPLEMENTING ARTIFICIAL INTELLIGENCE TECHNOLOGIES IN THE EDUCATIONAL PROCESS (Marketing Journal, 2025)
This article explores ways to improve the efficiency of integrating artificial intelligence (AI) technologies into the educational process. It analyzes AIʼs potential in personalizing learning, automating educational tasks, and creating interactive environ ments. The positive impact of digital tools on education quality and accessibility is emphasized. The study reviews Uzbekistanʼs ongoing reforms and international practices, highlighting the importance of modernizing pedagogical approaches and implementing AI-based methods in education.
Keywords: artificial intelligence; educational technologies; digital transformation; personalized learning; pedagogical methods; Uzbekistan; automation